PEDAGOG-TARBIYACHINING KASBIY MAHORATINI OSHIRISH TEXNOLOGIYASI - Reymbergenova, D.; Sultanova, N.; Tleumbetova, Q.D. (SCIENCE and SOCIETY, 2023)
In this article, we describe the basics of professional skill formation of pedagogues, who are mainly working in the field of preschool education, their tasks and technologies of professional skill improvement.